A Study of the Computer Literacy Skills of Mauritian Police Officers (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The main aim of this work was to study the computer literacy skills of officers of the Mauritian Police Force (MPF). At the same time, the results were used to demonstrate the impact of a short course in IT on them. To our knowledge, this is the first study of its kind. At the very beginning of the course, the officers were requested to take an online test which contained very basic questions on the course materials that they were going to cover. The same test was then administered to them on the last day of the training. The answers for the first test were not provided to them and they did not know that they would be required to take the test again on the last week. The results were collected and then compared. The mean score for the first test was 43.1% which increased to 69.2% on the last day. This clearly shows that the police officers have benefitted a lot from the course. The results of this study will provide important guidelines for the Government of Mauritius and the Commissioner of Police to know the strengths and weaknesses of its law enforce officers and this definitely help in the development of more appropriate commissioned courses.